Leg muscle power in 12-year-old black and white Tunisian football players - Ayed, K. B.; Latiri, I.; Dore, E.; Tabka, Z. (Research in Sports Medicine, 2011)
This study examined leg muscle power of young male Tunisian black and white football players and extended the analysis to determine whether there is a relationship between cycling peak power output (PPO) and some field tests. A total of 113 children (white group (WG) = n = 56; black group (BG) = n = 57) participated in this investigation. Anthropometric data included age, body mass (BM), height, leg length (LL), body mass index (BMI), and leg muscle volume (LMV). Cycling PPO was measured including a force-velocity test. Peak power output (PPO; W and W/kg), Fopt (optimal braking force), and Vopt (optimal velocity) were significantly higher in the WG compared with the BG (p < 0.05). However, jump and sprint performances of the BG were significantly higher than the WG (p < 0.05). Multiple stepwise regression with anthropometric variables and the extrapolated values of the force-velocity test as explanatory factors showed that 33% of the variance of PPO of BG was explained by qualitative factors that may be related to cycling skill, muscle composition, and socioeconomic and training status.